2005
DOI: 10.1007/s10722-004-4005-z
|View full text |Cite
|
Sign up to set email alerts
|

Variability and selection for morphological bean traits in wild cocoa trees (Theobroma cacao L.) from French Guiana

Abstract: Under the conditions prevailing at Paracou-Combi (French Guiana), 96 local wild cocoa trees belonging to ten populations from the Camopi and Tanpok rivers, and already pre-selected for other agronomic criteria, were characterized for their average fresh bean weight, an important selection criterion. Other traits, such as the average length and width of a bean, along with the percentage of flat beans, were also studied. The variability found for average fresh bean weight was substantial, with a coefficient of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 6 publications
3
4
0
Order By: Relevance
“…The usefulness of cluster analysis in grouping germplasm collection based on similar morphological variations as in the present study has been demonstrated in C. canephora (Aluka, 2013;Anim-Kwapong et al, 2011a), C. arabica (Gessese et al, 2015;Kebede and Bellachew, 2008;Montagnon and Bouharmont, 1996), and many other crop plants, such as cocoa (Aikpokpodion, 2010;Lachenaud and Oliver, 2005) sorghum (Ayana and Bekele, 1999), and rice (Arietta-Espinoza et al, 2005). The cluster analysis allowed for a successful grouping of the Robusta coffee genotypes into five main groups based on the similarity of 13 quantitative characters.…”
Section: Discussionsupporting
confidence: 62%
“…The usefulness of cluster analysis in grouping germplasm collection based on similar morphological variations as in the present study has been demonstrated in C. canephora (Aluka, 2013;Anim-Kwapong et al, 2011a), C. arabica (Gessese et al, 2015;Kebede and Bellachew, 2008;Montagnon and Bouharmont, 1996), and many other crop plants, such as cocoa (Aikpokpodion, 2010;Lachenaud and Oliver, 2005) sorghum (Ayana and Bekele, 1999), and rice (Arietta-Espinoza et al, 2005). The cluster analysis allowed for a successful grouping of the Robusta coffee genotypes into five main groups based on the similarity of 13 quantitative characters.…”
Section: Discussionsupporting
confidence: 62%
“…The least number of fresh beans pod -1 was recorded in genotype VTLC 1 (22.09). Similar findings on the variation of the number of beans pod -1 among different cocoa genotypes of different genetic origin were reported (Enriquez and Soria, 1968;Lachenaud and Oliver, 2005). In the present study, pods with more than 30 beans were observed in four genotypes viz., VTLCH 4 (30.33), VTLC 66 (30.38), VTLC 11 (32.07) and VTLC 19 (34.06).…”
Section: Pod and Bean Characters Of Cocoa Genotypessupporting
confidence: 91%
“… and the result was in tune with earlier workers[45,19]. High GCV value for single pod weight (59.38 %), wet bean weight per pod (51.13%), number of beans per pod (23.65%), single dry bean weight (41.38%), wet bean weight per plant per year (68.47%) dry bean weight per plant per year (70.artificial media.…”
supporting
confidence: 88%